2003
DOI: 10.1645/0022-3395(2003)089[0409:tsocbi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Two Species of Canine Babesia in Australia: Detection and Characterization by PCR

Abstract: The haemoprotozoan Babesia canis has been recognized in Australia for many years, and a second, smaller species has recently been discovered. Amplification and sequencing of a partial region of the 18S small subunit ribosomal RNA (rRNA) gene enabled detection and characterization of the large and small canine babesiae of Australia for the first time. Isolates from northern Australia were genetically characterized to be 99% homologous to Babesia canis vogeli, confirming previous speculation about the subspecies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(57 citation statements)
references
References 23 publications
2
52
1
2
Order By: Relevance
“…The primer sets PIRO A1 and PIRO B, which were described as being specific for Babesia spp. (JEFFERIES et al, 2003), showed a band that was about 500 bp greater than the Babesia band, and was also able to detect Hepatozoon species (O'DWYER et al, 2009). Similar results were obtained by Oyamada et al (2005) and Sasaki et al (2008).…”
Section: Molecular Diagnosissupporting
confidence: 77%
“…The primer sets PIRO A1 and PIRO B, which were described as being specific for Babesia spp. (JEFFERIES et al, 2003), showed a band that was about 500 bp greater than the Babesia band, and was also able to detect Hepatozoon species (O'DWYER et al, 2009). Similar results were obtained by Oyamada et al (2005) and Sasaki et al (2008).…”
Section: Molecular Diagnosissupporting
confidence: 77%
“…On the other hand, B. canis infection is distributed in Europe and Asia, including India and is capable of causing a wide range of clinical signs such as lethargy, anorexia, fever, jaundice, anemia and thrombocytopenia (Boozer and Macintire 2003). B. vogeli infection is distributed in the Northern and Southern America (Boozer and Macintire 2003), in Europe (Duh et al 2004), in Eastern and South Africa (Matjila et al 2004), Australia (Jefferies et al 2003) and Japan (Inokuma et al 2004) and leads to a relatively mild disease, often without evidence of clinical signs (Caccio et al 2002).…”
mentioning
confidence: 99%
“…The Babesia gibsoni was first described by Patton (1910) for pathogens occurring in dogs in India. This species has a global distribution and infections have been reported in Asia, Northern Africa, Middle East, United States, Australia, Brazil and Europe (Jefferies et al 2003;Zahler et al 2000a;Criado-Fornelio et al 2003a;Varshney et al 2003Varshney et al , 2004Varshney et al , 2008Trapp et al 2006;Hartelt et al 2007). Recent molecular researches have shown that Californian isolate of small Babesia is genotypically and phenotypically different from the B. gibsoni group and has thus been named Babesia conradae (Kjemtrup et al 2006).…”
mentioning
confidence: 99%
“…The recent knowledge based on genetic analyses of genes from canine piroplasms has shown that there are at least three distinct subtypes or subspecies for small piroplasms: a classic Asian type B. gibsoni; a small organism has been identified recently in northern Spain, which has been given the name Theileria annae; a small organism has been identified in California and remains unnamed [3,15,16,20,21]. Since the P50 gene is cloned from an Asian type B. gibsoni, an experiment is needed to evaluate whether the ELISA with GST-P50t can be used for detecting antibodies to T. annae or unnamed California type small piroplasm in dogs in Europe or North America.…”
Section: Discussionmentioning
confidence: 99%